Alcohol use among Nigerian university students: prevalence, correlates and frequency of use - Ajayi, Anthony Idowu (BMC Public Health, 2019)
BACKGROUND: Globally, alcohol use is responsible for 320 deaths every hour, and the impact is more among those in the younger age group. Despite the adverse health and social challenges associated with alcohol use, alcohol remains the most used and abused psychoactive substance among young adults. Our study aimed at determining the prevalence, correlates and frequency of alcohol use among young adults in two Nigerian universities. We further explored the role of family structure, family support and religion/religiosity on alcohol use in this study setting. Such findings could help to inform public health policy formulation in the country. METHODS: This was a cross-sectional study conducted in two selected universities in the North Central region of Nigeria. The study was conducted among a final sample of 784 students selected using stratified random sampling. An interviewer-administered questionnaire was used to collect data on ever and current alcohol use and frequency of alcohol use between February and April 2018. The data were analysed using descriptive and inferential statistics. RESULTS: The level of ever and current use of alcohol was 43.5 and 31.1%, respectively. The mean frequency of alcohol use among the study participants was three days, but ten days among current alcohol users. In the adjusted model, male sex, age above 19 years, infrequent attendance of religious rituals, and belonging to rich/middle-class family were significantly associated with a higher likelihood of ever use and current use of alcohol, while living in the same household as one’s father was associated with lower odds of current and ever use of alcohol. CONCLUSION: There is a high rate of lifetime and current use of alcohol among university students in the study setting. Alcohol use was significantly associated with living with parents, religion and religiosity. Both high and low socioeconomic status were associated with alcohol use. There is a need to implement measures in controlling alcohol manufacturing and marketing as well as policies regulating alcohol outlets establishment around educational institutions as well as the working hours in such outlets. Finally, there is a need to organise interventions aimed at reducing this unhealthy social norm among students in this setting.